Endoplasmic reticulum stress in skeletal muscle dysfunction of type 2 diabetes: mechanisms and therapeutic implications - Wang, Xin; Li, Mingdi; Chi, Zengpeng; Wang, Mingshan; Liu, Jiayi; Li, Ailin; Song, Bailin; Tong, Le (Frontiers in Endocrinology, 2026)
With the continuous rise in the global prevalence of type II diabetes mellitus (T2DM), the associated skeletal muscle complications, including insulin resistance, muscle atrophy, and physical frailty, have garnered increasing attention. Skeletal muscle plays a vital role as a metabolic and endocrine organ and is considered a key factor in the pathological mechanisms of T2DM. Despite significant advances in understanding, the intrinsic molecular mechanisms underlying skeletal muscle dysfunction remain incompletely elucidated. Recent studies have highlighted a significant cellular stress response known as endoplasmic reticulum stress (ERS), which is triggered by hyperglycemia, lipotoxicity, and inflammation, and may serve as a pivotal hub in T2DM pathology. This review narratively examines published articles from the past five years, focusing on experimental studies related to ERS and T2DM myopathy. Comprehensive searches were conducted in electronic databases for journal articles published between 2020 and 2025.This review synthesizes experimental studies to elucidate how ERS disrupts muscle homeostasis via the unfolded protein response (UPR) pathways (PERK, IRE1α, and ATF6) contributing to insulin resistance and activation of protein degradation systems. Consequently, intervention strategies targeting ERS may offer new insights and directions for the prevention and treatment of T2DM-related muscle disorders. This review aims to explore the mechanisms by which ERS contributes to T2DM myopathy, identifying potential therapeutic targets and providing a foundation for future clinical research.